2021
DOI: 10.3390/ijerph18020428
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Evidence-Based Public Policy and Practice: Analysis of the Determinants of Personal/Public Adaptation and Mitigation Behavior against Particulate Matter by Focusing on the Roles of Risk Perception, Communication, and Attribution Factors

Abstract: In recent years, awareness about the risk of particulate matter (PM) has increased both domestically and internationally; consequently, various policies have been implemented to reduce PM. Since citizens are both victim and cause of this risk, PM cannot be successfully decreased only through government policies. Therefore, citizens’ active participation is required to reduce PM and prevent its risks. However, a theoretical model about public behavior against PM has not been established. Therefore, we suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…These findings provide essential enlightenment for guiding rational public behavior and managing public opinion during emergencies. Besides, an exploratory theoretical model of four public behaviors based on the combinations of the public-personal domains and mitigation-adaptation actions was suggested against the risk of particulate matter (PM, a small air pollutant) by focusing on the roles of risk perception, communication, and attribution factors [ 21 ]. These results provide some enlightenment effect on selecting public behavioral factors and classifying behavioral coping strategies in our research.…”
Section: Literature Review and Analysis Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings provide essential enlightenment for guiding rational public behavior and managing public opinion during emergencies. Besides, an exploratory theoretical model of four public behaviors based on the combinations of the public-personal domains and mitigation-adaptation actions was suggested against the risk of particulate matter (PM, a small air pollutant) by focusing on the roles of risk perception, communication, and attribution factors [ 21 ]. These results provide some enlightenment effect on selecting public behavioral factors and classifying behavioral coping strategies in our research.…”
Section: Literature Review and Analysis Frameworkmentioning
confidence: 99%
“…However, the previous theories and models (TPB, cognition-affect theory) lack specificity in the context of COVID-19 crisis, and the specific public behavior theories were rarely reported. Furthermore, traditional statistical methods, such as principal component analysis, linear regression model, and path analysis [ 17 , 18 , 20 , 21 ], only clarify the quantitative correlation between the dependent and independent variables and cannot profoundly explain its further logical causality, which limits the theory’s explanatory power.…”
Section: Literature Review and Analysis Frameworkmentioning
confidence: 99%
“…Second, in terms of theoretical frameworks, as causal factors influencing the intention and action toward PM, previous studies adopted the psychometric paradigm, known as the risk perception paradigm [ 3 , 27 ]. This paradigm was proposed by Slovic et al [ 28 ].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…For example, mainly based on the psychometric paradigm, Jung and Kim [ 27 ] showed how not only self-efficacy, personal norms, information source credibility, psychological distance, and commitment to action but also perceived risk, perceived benefit, trust, and knowledge influence the judgement and action toward PM. In addition, Kim et al [ 3 ] showed that risk perception, communication, and attribution significantly influence the person or public mitigation and adaptation. In particular, perceived benefit, perceived risk, negative emotion, the receiver’s ability, and external attribution have an impact on them.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation